2015
DOI: 10.1186/s13089-015-0030-8
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasonography improves the diagnosis of splenomegaly in hospitalized patients

Abstract: BackgroundIt is important to detect splenomegaly as it can have important diagnostic implications. Previous studies, however, have shown that the traditional physical examination is limited in its ability to rule in or rule out splenomegaly.ObjectiveTo determine if performing point-of-care ultrasonography (POCUS) in addition to the traditional physical examination improves the sensitivity and specificity for diagnosing splenomegaly.MethodsThis was a prospective trial of diagnostic accuracy. Physical and sonogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…Seventeen core ultrasound competencies have been identified and they are shown in Table 1 [12][13][14][15][16][17][18][19][20].…”
Section: Core Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen core ultrasound competencies have been identified and they are shown in Table 1 [12][13][14][15][16][17][18][19][20].…”
Section: Core Competenciesmentioning
confidence: 99%
“…The presence of a collapsable IVC, normal right ventricle and collapsing LV, in the absence of aortic abnormality suggests hypovolemic or distributive (likely septic) shock. On the other hand, the presence of left ventricular dysfunction suggests cardiogenic shock and the presence of right Table 1 Core competencies (p/a = present / absent) [12][13][14][15][16][17][18][19][20]. [31].…”
Section: Patients With Shock Of Unknown Origin and Peri-arrest Situatmentioning
confidence: 99%
“…23 In a recent study, with limited training of less than 1 hour in duration on the use of point-of-care sonography, participants using both point-of-care sonography and physical examination techniques were able to improve sensitivity in diagnosing splenomegaly in hospitalized patients. 24 We have previously demonstrated that with limited training, medical residents' measurements of spleen size correlated strongly and significantly with sonographers' measurements. 25 Although longitudinal measurements of spleen size are the reference standard, this approach may pose a challenge to novice sonographers.…”
mentioning
confidence: 92%
“…With the increased availability of portable ultrasound technology, there may be a role for bedside sonography in the detection of splenomegaly . In a recent study, with limited training of less than 1 hour in duration on the use of point‐of‐care sonography, participants using both point‐of‐care sonography and physical examination techniques were able to improve sensitivity in diagnosing splenomegaly in hospitalized patients . We have previously demonstrated that with limited training, medical residents' measurements of spleen size correlated strongly and significantly with sonographers' measurements …”
mentioning
confidence: 99%
“…Splenomegaly is also an important finding for physicians, and like hepatomegaly, physical examination is of low sensitivity and specificity in diagnosing it (3). And alike, biomedical imaging is of importance.…”
Section: Introductionmentioning
confidence: 99%